Phosphoglyceride crystal deposition disease in the abdominal wall: a case report - Osamu Nakahara; Hideo Baba (Surgical Case Reports)
Abstract Background Phosphoglyceride crystal deposition disease (PGDD) is characterized by phosphoglyceride crystal deposition that simulates neoplasia in soft tissue scars or bone. Reports of PGDDs are rare. Here, we present the case of a patient with PGDD in the abdominal wall. Case presentation A 57-year-old Japanese man with worsening right lower abdominal pain had no significant family or occupational history. Laboratory data showed elevated inflammatory markers with a white blood cell count of 14,400 × 109/L and C-reactive protein of 11.8 mg/L, but no other abnormalities. Helical computed tomography (CT) revealed a tumor in the abdominal wall (longest dimension, approximately 10 cm). Positron emission tomography–CT revealed fluorodeoxyglucose accumulation in the mass only (SUVmax, 41). Clinical and radiographic findings suggested malignant lymphoma, undifferentiated sarcoma, or liposarcoma. He underwent exploratory laparotomy and further treatment. At surgery, we found a huge milky-whitish mass with a rough surface in the transversus abdominis. Complete resection was performed and his postoperative recovery was good. Surprisingly, the final pathologic diagnosis was phosphoglyceride crystal deposition disease with the characteristic crystal deposition in a corolla shape, histiocytic reaction with abundant foreign-body-type giant cells, and no evidence of neoplasia. The patient remains asymptomatic with no disease recurrence. Conclusion Although phosphoglyceride crystal deposition disease in the abdominal wall is rarely encountered in clinical practice, its inclusion in differential diagnosis is important. Given the occurrence at sites of invasive procedures, we believe efforts to reduce invasiveness when performing surgery and follow-up for early detection of recurrence are important.